2019
DOI: 10.3390/s19225046
|View full text |Cite
|
Sign up to set email alerts
|

Body Dimension Measurements of Qinchuan Cattle with Transfer Learning from LiDAR Sensing

Abstract: For the time-consuming and stressful body measuring task of Qinchuan cattle and farmers, the demand for the automatic measurement of body dimensions has become more and more urgent. It is necessary to explore automatic measurements with deep learning to improve breeding efficiency and promote the development of industry. In this paper, a novel approach to measuring the body dimensions of live Qinchuan cattle with on transfer learning is proposed. Deep learning of the Kd-network was trained with classical three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(12 citation statements)
references
References 66 publications
1
10
0
1
Order By: Relevance
“…Measuring horses is more difficult than measuring cows because the more an object moves, the more difficult it is to measure. The accuracy of the present study was almost equivalent to that of a study by Cozler et al [4] and slightly lower than those of studies by Huang et al [9,10]. Even a horse that moves frequently can be made to stay still for a short time.…”
Section: Discussionsupporting
confidence: 53%
See 3 more Smart Citations
“…Measuring horses is more difficult than measuring cows because the more an object moves, the more difficult it is to measure. The accuracy of the present study was almost equivalent to that of a study by Cozler et al [4] and slightly lower than those of studies by Huang et al [9,10]. Even a horse that moves frequently can be made to stay still for a short time.…”
Section: Discussionsupporting
confidence: 53%
“…In a study measuring 30 Holstein dairy cows using a 5-camera system, the correlation coefficients between manual and 3D measurements were 0.89 for ChD, 0.82 for HWi, 0.78 for GiC, 0.76 for backside width, 0.63 for ischial width, and 0.62 for WCr [4]. Huang et al [9,10] used a non-contact body dimension measurement approach for Qinchuan cattle using a LiDAR system and found that the final deviations were close to 2 mm and within approximately 2%. Measuring horses is more difficult than measuring cows because the more an object moves, the more difficult it is to measure.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The volumetric measurements are rough approximations given the limited camera views of either the top or the side of an animal. The shape descriptors reported in the literature include generic ones such as Fourier descriptors ( Fernandes et al, 2019 ) and fast point feature histograms ( Huang et al, 2019 ).…”
Section: Methods For Morphometric Measurements Extractionmentioning
confidence: 99%